Responsive public complaint service innovation:The JAKI Application case in DKI Provincial Government - Ernawati, Deasy; Dwiarto, Raden; Aini, Yulia Nurul; Asropi, Asropi; Harsiwi, Noviana Dwi (Universitas Merdeka Malang, 2023)
JAKLAPOR is one of the features in the DKI Provincial Government’s JAKI application, which serves as the official complaint channel for DKI residents. The public has lodged complaints after using the JAKI application. However, there are numerous flaws in the JAKI application that can impede public use of the JAKLAPOR feature. The purpose of this study is to ascertain the level of public satisfaction with the JAKLAPOR feature. This study employs a mixed methods approach with an explanatory sequential mixed methods design. The quantitative and qualitative methods are used sequentially in this design to produce a comprehensive study on community satisfaction with the JAKLAPOR feature. The study’s findings indicate that the community is pleased with the JAKLAPOR feature as a channel for public complaints. In this case, the informant felt that the UPTD responded quickly enough to public complaints reported through JAKLAPOR. Rapid response accompanied by reasonably good completion quality. However, JAKPLAPOR service improvement must be continuous, including more intensive public outreach about the existence of the JAKLAPOR feature in the JAKI application.